Discrete element method models of elastic and elastoplastic fiber assemblies. Issue 8 (15th May 2021) - Guo, Yu; Liu, Qingzhao; Li, Yanjie; Li, Zhenhua; Jin, Hanhui; Wassgren, Carl; Curtis, Jennifer S.
Abstract: Geometry‐dependency and plasticity are considered in the contact force models for the discrete element method simulations of elastic and elastoplastic fiber assemblies subject to uniaxial compression. It is observed that the contact force models have a significant impact on compressive loads. A simplified normal contact force model leads to smaller loads at large solid volume fractions compared to the experimental results, while the present geometry‐dependent models give better predictions. Simulations with a simple Coulombic tangential contact force model (considering sliding friction only) significantly underestimate the loads, while a Mindlin tangential force model that considers static friction improves the predictions. For the modeling of the fibers that undergo large plastic deformations, plasticity should be considered for both the fiber bending and fiber–fiber normal contact in order to obtain correct simulation results. Elastic models for fiber–fiber contact and fiber bending deformation remarkably overpredict the loads for the plastic fibers.